Acute hydrogen sulfide-induced neurochemical and morphological changes in the brainstem. (February 2023) - Santana Maldonado, Cristina M.; Kim, Dong-Suk; Purnell, Benton; Li, Rui; Buchanan, Gordon F.; Smith, Jodi; Thedens, Daniel R.; Gauger, Phillip; Rumbeiha, Wilson K.
Abstract: Hydrogen sulfide (H2 S) is a toxin affecting the cardiovascular, respiratory, and central nervous systems. Acute H2 S exposure is associated with a high rate of mortality and morbidity. The precise pathophysiology of H2 S-induced death is a controversial topic; however, inhibition of the respiratory center in the brainstem is commonly cited as a cause of death. There is a knowledge gap on toxicity and toxic mechanisms of acute H2 S poisoning on the brainstem, a brain region responsible for regulating many reflective and vital functions. Serotonin (5-HT), dopamine (DA), and γ-aminobutyric acid (GABA) play a role in maintaining a normal stable respiratory rhythmicity. We hypothesized that the inhibitory respiratory effects of H2 S poisoning are mediated by 5-HT in the respiratory center of the brainstem. Male C57BL/6 mice were exposed once to an LCt50 concentration of H2 S (1000 ppm). Batches of surviving mice were euthanized at 5 min, 2 h, 12 h, 24 h, 72 h, and on day 7 post-exposure. Pulmonary function, vigilance state, and mortality were monitored during exposure. The brainstem was analyzed for DA, 3, 4-dehydroxyphenyl acetic acid (DOPAC), 5-HT, 5-hydroxyindoleatic acid (5-HIAA), norepinephrine (NE), GABA, glutamate, and glycine using HPLC. Enzymatic activities of monoamine oxidases (MAO) were also measured in the brainstem using commercial kits. Neurodegeneration was assessed using immunohistochemistry and magnetic resonance imaging. Results showed that DA and DOPAC were significantly increased at 5 min post H2 S exposure. However, by 2 h DA returned to normal. Activities of MAO were significantly increased at 5 min and 2 h post-exposure. In contrast, NE was significantly decreased at 5 min and 2 h post-exposure. Glutamate was overly sensitive to H2 S-induced toxicity manifesting a time-dependent concentration reduction throughout the 7 day duration of the study. Remarkably, there were no changes in 5-HT, 5-HIAA, glycine, or GABA concentrations. Cytochrome c oxidase activity was inhibited but recovered by 24 h. Neurodegeneration was observed starting at 72 h post H2 S exposure in select brainstem regions. We conclude that acute H2 S exposure causes differential effects on brainstem neurotransmitters. H2 S also induces neurodegeneration and biochemical changes in the brainstem. Additional work is needed to fully understand the implications of both the short- and long-term effects of acute H2 S poisoning on vital functions regulated by the brainstem. Highlights: ● H2 S, a neurotoxicant, suppresses breathing ● H2 S poisoning increases MAO-A and MAO-B activity in the brainstem ● Acute H2 S exposure increases DA and DOPAC, but reduces glutamate and NE concentrations in the brainstem ● H2 S induces neurodegeneration in select regions of the pons and medulla starting 72 h post-exposure ● Neurodegeneration in brainstem may have long-term health implications